2018
DOI: 10.3389/fpls.2018.00122
|View full text |Cite
|
Sign up to set email alerts
|

Plant Abiotic Stress Proteomics: The Major Factors Determining Alterations in Cellular Proteome

Abstract: HIGHLIGHTS: Major environmental and genetic factors determining stress-related protein abundance are discussed.Major aspects of protein biological function including protein isoforms and PTMs, cellular localization and protein interactions are discussed.Functional diversity of protein isoforms and PTMs is discussed.Abiotic stresses reveal profound impacts on plant proteomes including alterations in protein relative abundance, cellular localization, post-transcriptional and post-translational modifications (PTM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
162
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(175 citation statements)
references
References 162 publications
(237 reference statements)
10
162
0
3
Order By: Relevance
“…Plant tolerance to water deficit requires the ability to maintain functions under unfavorable water conditions and to recover water status and functions rapidly after rewatering. Recent studies showed that recovery phase is as important as the stress treatment since the efficient recovery affects further plant growth and development (Chen et al 2016, Kosová et al 2018. Significant variations in responses to drought stress and in mechanisms of recovery after rehydration were revealed in varieties with different drought tolerance (Hayano-Kanashiro et al 2009, Cruz de Carvalho et al 2011, Foster et al 2015, Sun et al 2016, Kosová et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Plant tolerance to water deficit requires the ability to maintain functions under unfavorable water conditions and to recover water status and functions rapidly after rewatering. Recent studies showed that recovery phase is as important as the stress treatment since the efficient recovery affects further plant growth and development (Chen et al 2016, Kosová et al 2018. Significant variations in responses to drought stress and in mechanisms of recovery after rehydration were revealed in varieties with different drought tolerance (Hayano-Kanashiro et al 2009, Cruz de Carvalho et al 2011, Foster et al 2015, Sun et al 2016, Kosová et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using proteomic methods are therefore essential for revealing, not only the role of proteins in complex mechanisms of drought response in common bean, but also for pointing out possible molecular markers of drought tolerance. These methods not only enable identification of proteins with abundance changed in response to environmental stress, but also the detection of protein complexes and protein localization, as well as of post-translational protein modifications related to a specific stress factor [70][71][72] as reported later in this chapter. As underlined above, this approach has experienced rapid development by the recent publishing of full genome sequences of many plants, among them common bean [50].…”
Section: Proteome Analysis Of Drought Responsementioning
confidence: 99%
“…Posttranslational modifications, one of the major factors determining protein biological function [31], can regulate protein activity, localization, and protein-protein interactions, leading to fine-tuning of plant responses to various external stimuli to mitigate potential damage from environmental stress [32]. The results of PTMs prediction of PheCPAs family proteins are shown in Table 2.…”
Section: Posttranslational Modifications Prediction Of Phecpa Proteinsmentioning
confidence: 99%